Migration, diversity and the arts : the postmigrant condition - Schramm, Moritz, 1970-; Moslund, Sten Pultz; Petersen, Anne Ring; Gebauer, Mirjam; Post, Hans Christian; Vitting-Seerup, Sabrina; Wiegand, Frauke (Routledge research in art and politics., 2019)
This book offers a compelling study of contemporary developments in European migration studies and the representation of migration in the arts and cultural institutions. It introduces scholars and students to the new concept of 'postmigration', offering a review of the origin of the concept (in Berlin) and how it has taken on a variety of meanings and works in different ways within different national, cultural and disciplinary contexts. The authors explore postmigrant theory in relation to the visual arts, theater, film and literature as well as the representation of migration and cultural diversity in cultural institutions, offering case studies of postmigrant analyses of contemporary works of art from Europe (mainly Denmark, Germany and Great Britain).